Professional-Public Mechanisms Assess the Qualifications of Educators - Egorov I.A; Yamburg E.S; Akhapkina M.E; Volkova A.A; Katrenko O.N; Kocherejko S.S; Odintsova N.N (Moscow State University of Psychology and Education, 2018)
The article describes the progress of work on the project "Professional and public mechanisms for assessing the qualifications of educators " implemented by the Pedagogical Association «XXI century educator» using the grant of the President of the Russian Federation for the development of civil society provided by the Foundation for Presidential Grants (No. 17-1-008266) and its main results. Based on the current achievements of Russian and foreign pedagogical science and practice, in accordance with the professional standard of the educator and taking into account the current formation and introduction of the national system of teacher growth, proposals have been developed for assessing the qualifications (labor actions) of educators in the form of draft normative legal act and methodological recommendations. The necessity of active and wide participation of the professional pedagogical community in the organization and evaluation of the qualification of pedagogical workers as a necessary condition for building an effective system ensuring the professional growth of educators is substantiated.